Assessment of Psychological Distress and Its Related Factors Among Breast Cancer Patients In A Tertiary Cancer Center of Nepal - Thapa, Usha; Pokhrel, Manju; Kafle, Rukmini; Yadav, Sabita (Nepalese Journal of Cancer, 2025)
Introduction: Breast cancer is the most prevalent cancer and the leading cause of cancer death worldwide. The diagnosis and treatment of breast cancer can be significantly stressful events that cause psychological distress. Worldwide, the prevalence of psychological distress among breast cancer patients was significantly high. But, in the context of Nepal, there was a scarcity of research on psychological distress in breast cancer patients. Therefore, this study aims to investigate the prevalence of psychological distress and its related factors in breast cancer patients Methods: This cross-sectional study was conducted among 260 breast cancer patients at a tertiary cancer center in Nepal. Psychological distress was assessed by utilizing the NCCN Distress Thermometer along with the Problem List. Descriptive statistics were used to analyze the variables by using SPSS version 22. Results: The study included a total of 260 women, with an average age of 47.97 ± 11.087. Almost all respondents (98.1%) were married, and 64.6% lived in joint family structures, with 51.5% of them being illiterate. In addition, 53.7% had been diagnosed within 6 months, and 64.6% were in the early stage of breast cancer. The majority (83.8%) of respondents had experienced a significant level of distress. The most common factors related to distress included fatigue (78.40%), worry (77.10%), pain (72.0%), fear (67.9%), sleep disturbances (66.5%), and sadness (64.2%). Conclusion: This study indicated that the majority (83.8%) of patients diagnosed with breast cancer at the tertiary cancer center of Nepal experience significant levels of psychological distress. The most prevalent factors related to distress are fatigue, anxiety, pain, fear, and sleep disturbances. It is recommended to implement regular screenings and address the associated factors promptly to alleviate distress and enhance quality of life.